Praktek Pengupahan Penjaga Pasar Dalam Perspektif Hukum Positif Dan Hukum Islam (Studi Kasus di Pasar Karang Bulayak Praya Lombok Tengah) - Parida Angriani (PT FORMOSA CENDEKIA GLOBAL, 2022)
Employment in Indonesia is a familiar phenomenon among the public. Sometimes this phenomenon reaps the pros and cons in the midst of society. The research method used is field research with a qualitative research. The data collection technique used in this research is to use observation techniques and interviews. The research approach uses a normative-juridical approach that refers to positive legal norms and Islamic law. The results of the research obtained in the practice of wages in the Karang Bulayak market Praya Central Lombok, were studied with a positive legal perspective and Islamic law had been fulfilled in accordance with Clause 1338 of KUHPerdata, Clause 1328 of KUHPerdata, the terms and pillars of ijarah.